New agents in treatment of metastatic renal cell carcinoma - Żołnierek, Jakub; Nurzyński, Paweł; Rzepecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2007)
As renal cell carcinoma appears to be resistant to conventional treatment modalities and results of cytokine-based immunotherapy are far from satisfactory, there is desperate need for new active agents to be discovered. Introduction of advanced techniques of molecular biology into practice helped to establish the potent role of membrane receptors for growth factors, especially its component with activity of thyrosine kinases in growth, proliferation, invasion and formation of metastatic lesions. These molecules became therapeutic targets. It seems that thyrosine kinase inhibitors will be an alternative to cytokines and the basis of second line treatments for patients who failed to benefit from immunotherapy. Those most investigated and advanced in clinical trials are CCI-771 (temsirolimus), Avastin (bevacizumab), BAY 43-9006 (sorafenib) and SU 011248 (sunitinib). The latter two have already been formally approved for treatment of patients with renal cell carcinoma. The article is a short review of the literature with special attention paid to clinical data.